Lower Motor Neuron Findings after Upper Motor Neuron Injury: Insights from Postoperative Supplementary Motor Area Syndrome - Florman, Jeffrey E.; Duffau, Hugues; Rughani, Anand I. (Frontiers in Human Neuroscience, 2013)
Hypertonia and hyperreflexia are classically described responses to upper motor neuron injury. However, acute hypotonia and areflexia with motor deficit are hallmark findings after many central nervous system insults such as acute stroke and spinal shock. Historic theories to explain these contradictory findings have implicated a number of potential mechanisms mostly relying on the loss of descending corticospinal input as the underlying etiology. Unfortunately, these simple descriptions consistently fail to adequately explain the pathophysiology and connectivity leading to acute hyporeflexia and delayed hyperreflexia that result from such insult. This article highlights the common observation of acute hyporeflexia after central nervous system insults and explores the underlying anatomy and physiology. Further, evidence for the underlying connectivity is presented and implicates the dominant role of supraspinal inhibitory influence originating in the supplementary motor area descending through the corticospinal tracts. Unlike traditional explanations, this theory more adequately explains the findings of postoperative supplementary motor area syndrome in which hyporeflexia motor deficit is observed acutely in the face of intact primary motor cortex connections to the spinal cord. Further, the proposed connectivity can be generalized to help explain other insults including stroke, atonic seizures, and spinal shock.